Ageing and the Grey Society: an Opportunity to Change Our Views in Medicine? - Alessandro Vercelli; Ludovico Ciferri (DigitCult@Scientific Journal on Digital Cultures, 2018)
Population ageing will increase spending on health care and long-term care. According to the projections in the 2018 Ageing Report, spending on health care and long-term care as a percentage of gross domestic product (GDP) is projected to rise by an average of 0.7 and 1.3 percentage points respectively over the period 2013-60. As life expectancy increases, the individual, social and financial burden of assisting these disabled patients will particularly grow in developed countries. Therefore, we must rethink the approach to ageing and neurodegenerative diseases according to current needs and new challenges. We need a personalized approach to the single subject: as shown in other fields, such as oncology, this approach may lead to an improved efficacy in treatments and also in significant economic outcome. To this aim Information and Communication Technology (ICT) and Artificial Intelligence (AI) are two major innovative tools which may support healthy ageing and precision medicine in the elderly, reducing the economic costs of care.